IODINE OF SCARCITY PREVENTION FOR REGULATORY DOCUMENTS IMPROVEMENT AND HIS POPULATION TO HEALTH EFFECT (Proceedings of International Educators Conference, 2024)
Iodine deficiency is very common worldwide, primarily in underdeveloped countries (Figure 1). Iodine is very important in the early stages of fetal brain development. In 2017 to 38 million in the world near baby iodine shortage with to the world came​ of the world heavy​ iodine shortage has been in the regions by an average of 13.5 points in intellect coefficient (IQ) decrease in ​the 2010 year to the situation according to World Health Organization (WHO). Shortage because of whole the world in 187 million people across bully appears that it was guessed did​ Iodine lack of Africa, Southeast Asia and Western Calm down the ocean in countries the most a lot occurs. Endemic goiter according to heavy endemic in places where 5% of the population is mental in 15% weakness risk increase possibility determined. Iodine shortage population health and to well-being serious effect doer from problems one is considered Iodine thyroid get rid of stable performance and brain development for necessary especially​​​ young children and pregnant women health for important importance occupation is enough.